Cathode surface microrelief formation at the electron explosion emission; Proceedings of VIIth International Symposia on Discharge and Electrical Insulation in Vacuum, Novosibirsk, 1976 - Mesyats G. A. Gennady Andreyevich (1976, 1976)
В фонде НТБ ТПУ отсутствует